FRUSTRATION AND DEPRESSION CONDITIONS OF ENTREPRENEURS INVOLVED IN BUSINESS ACTIVITY - Podzorov, I.Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The article discusses problems of adaptation of specialists changed their activity for small-scale business field forcedly, particularly determined are their mental conditions with the help of tests. The special attention is paid to the level of their frustration, aggressiveness, emotional exhausting, as well as a range of other indicators. The research has been conducted in three different groups, while data obtained are characterised both separately for every group and as a whole to determine the main trend.Obtained results are characterized by high level of frustration, depression, aggression and emotional burnout (more specifically characterized components such as emotional exhaustion and reduction of personal attainments). Such negative showings are characteristic not just for separate groups but for the whole mass of specialists as well.